Junior worldmark encyclopedia of world cultures. Volume 6, Mauritania to Nigeria - Gall, Susan B.; Gall, Timothy L. (Detroit, Mich. : UXL, 1998)
Volume six of a nine volume, alphabetically-arranged set that profiles the different world cultures; includes information on the ethnology and human geography of countries from Mauritania to Nigeria.
Includes bibliographical references and index.
5-8
Keywords: Ethnology -- Encyclopedias, Juvenile; Human geography -- Encyclopedias, Juvenile; Ethnology -- Encyclopedias; Human geography -- Encyclopedias; Ethnology -- Encyclopedias; Human geography -- Encyclopedias